Optimalisasi Mutu Pembelajaran Berbasis Revolusi Industri 4.0 pada Program Studi Kedokteran Hewan Universitas Nusa Cendana - Dede Rival Novian; Aji Winarso (Universitas Mathla'ul Anwar Banten, 2020)
OPTIMIZATION OF LEARNING QUALITY BASED ON INDUSTRIAL REVOLUTION 4.0 IN THE VETERINARY MEDICINE PROGRAM OF UNIVERSITAS NUSA CENDANA. Innovation activities carried out aim to find out the main issues that become problems at the Faculty of Veterinary Medicine, University of Nusa Cendana. The method used in determining the main principle is the Urgency, Seriousness, Growth method. Based on this analysis, the most appropriate contemporary issue to be raised is that the optimization of learning based on the industrial revolution 4.0 is not yet optimal within the Faculty of Veterinary Medicine. If the issue is left then the quality of the institution will decrease. Therefore, innovation activities are needed to overcome these issues. There are four innovation activities carried out. The first is the determination of the main issues, the second is to provide assistance for lecturers regarding digitalization of teaching materials, assisted by the quality assurance group of the Faculty of Veterinary Medicine, the third is the preparation of e-learning based learning designs, and the fourth is the collection and preparation of e-learning based learning materials. The result of this activity is the use of digitizing learning in veterinary study programs. This activity has an impact on the development of e-learning learning in veterinary study programs at the University of Nusa Cendana by increasing the participation of lecturers and students in using e-learning at the Faculty of Veterinary Medicine, University of Nusa Cendana. Through this activity, learning is more creative and innovative based on the industrial revolution 4.0.